Mengenal Bidang Garapan Manajemen Dalam Lembaga Pendidikan Islam - Muhammad Muhammad; Ramdanil Mubarok (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the concept of management, the management concept of educational institutions, and the management field in Islamic educational institutions. The method used in research is Library research. As a result, the concept of management is the process of planning, organizing, guiding, and controlling resources to achieve established objectives. In contrast, the management concept of educational institutions is the application of management concepts in the context of education that involves the management of various administrative, academic, and operational aspects of the educational institution to achieve established educational objectives. In the context of Islamic educational institutions, management involves the management of special aspects related to Islamic education, such as the curriculum of religion, the teaching and learning of Islam, the development of the character and morality of students by Islamic values, as well as the administration of facilities that support Islamic education. With a better understanding of the field of management in Islamic institutions of education, we are expected to be better prepared to meet the dynamics and demands of the times in developing Islamic quality and relevant education.